Endoscopic ultrasound combined with submucosal saline injection for differentiation of T1a and T1b esophageal squamous cell carcinoma: a novel technique - Li, J.-J.; Shan, H.-B.; Gu, M.-F.; He, L.; He, L.-J.; Chen, L.-M.; Luo, G.-Y.; Xu, G.-L. (Endoscopy, 2013)
Endoscopic ultrasound (EUS) is the optimum method for investigation of early esophageal squamous cell carcinoma (ESCC). However, it is difficult to substage early ESCC as T1a or T1b. The aim of this study was to improve the staging accuracy of early ESCC by using EUS combined with submucosal saline injection (SSI). The study enrolled 15 patients with suspected early ESCC who were examined by EUS and subsequently by SSI combined with EUS. The patients then underwent endoscopic or surgical resection within 10 days. The accuracy of EUS staging (alone or following SSI) was evaluated and compared with the pathological results postoperatively. No severe complications of the SSI arose. EUS plus SSI easily distinguished the mucosa from the lesion and the submucosa because of the low-echoic saline-filled cushion in the submucosa. The accuracy of SSI combined with EUS for staging T1a or T1b was 86.7 %, which was better than that using EUS alone (60.0 %).